2001
DOI: 10.1063/1.1370995
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the radiative recombination zone in InGaN/GaN multiple quantum well light-emitting diodes

Abstract: The temperature dependence of the radiative recombination zone in InGaN/GaN multiple quantum well light-emitting diodes is investigated. From the electroluminescence spectra measured at various temperatures, it is found that there are two peaks at about 400 and 460 nm, which can be assigned as Mg-related and quantum well transitions, respectively. The behavior of these two peaks with temperature is modeled by the two rate equation. Based on this model, we deduce the activation energy of Mg in GaN films to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…Furthermore, an additional band existed at 390 nm and was tentatively attributed to the Mgrelatively transition owing to the recombination zone shifts to the p-type GaN region. [18,19]. The carriers captured in the LEDs with InGaN/GaN and GaN barriers also showed a sharp difference owing to the enhanced carrier confinement caused by InGaN/GaN barriers.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, an additional band existed at 390 nm and was tentatively attributed to the Mgrelatively transition owing to the recombination zone shifts to the p-type GaN region. [18,19]. The carriers captured in the LEDs with InGaN/GaN and GaN barriers also showed a sharp difference owing to the enhanced carrier confinement caused by InGaN/GaN barriers.…”
Section: Resultsmentioning
confidence: 91%
“…A leading blue MQW emission band is observed at nearly 440 nm (2.8 eV) with fine structures owing to the Fabry-Perot fringes. Furthermore, an additional band exists at 400 nm (3.1 eV) and is tentatively attributed to the Mg-relative transition [5,12]. The two peaks of 400 and 440 nm are named the high-and low-energy bands in this work.…”
Section: Resultsmentioning
confidence: 94%
“…Previous works have reported that the localized radiative centers which may originate from In-rich regions may be responsible for this phenomenon by using optical and electrical measurements [2][3][4]. Some investigations have found that InGaN quantum well (QW) LEDs have an unusual temperaturedependent electroluminescence (EL) characteristic and furthermore, have found an additional higher energy band ($400 nm) at low temperature, which can be assigned as Mg-related emission [5,6].…”
Section: Introductionmentioning
confidence: 97%
“…24 Recently, an anomalous temperature-dependence of electroluminescence intensity in GaN-based LEDs was reported. [27][28][29][30] It was found that when temperature is decreased to around 200 K, the EL intensity rises, as expected from the improved quantum efficiency. However with a further decrease in temperature, the EL intensity falls dramatically.…”
Section: Discussionmentioning
confidence: 74%
“…That phenomenon was explained by reduced carrier capture by QWs at low temperature, [27][28][29] or by the low ionization rate of magnesium (Mg) in p-GaN at low temperature. 30 In our simulation, Fig. 8 reveals that the electron non-capture is much stronger at low temperature due to the weaker electron-LO-phonon scattering, which leads to the weak EL intensity below 200k, but it does not grow worse with a further fall in temperature, indicating that the weak EL intensity is nearly temperature-independent over the low temperature range (below 200 K).…”
Section: Discussionmentioning
confidence: 79%